PENGARUH MODAL USAHA TERHADAP KINERJA PELAKU USAHA DI KECAMATAN ULUNOYO - Vinsen Laia (Universitas Nias Raya, 2023)
The type of research used is a quantitative type of causal nature. The source of the data was from a photocopying business in Telukdalam District, with the population and sample in this study being 31 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is a simple linear regression analysis. The results of this study showed that the counting value of 4,358 >ttabel was 1,549. This research can be concluded that there is an influence of entrepreneurial motivation on the income of the Fotokopy business in Telukdalam District. The suggestions of this study are (1) To increase business income, it is presumed that the owner of the photocopy provides good service and presumably completes the product so that consumers are not disappointed when they want to make a purchase. (2) Presumably store owners, increase their creativity to meet consumer needs in increasing business income.